The Impact of Intellectual Capital, Credit Risk and Corporate Social Responsibility on Banks’ Profitability: Empirical Analysis of the Selected Malaysian Islamic Banks - Kim Peong, Kwee; Nadia Mahfuz, Norseri; Peng Peong, Kwee (International Journal of Engineering and Technology, 2018)
The present research provides new empirical evidence on the impact of bank-specific characteristic factors (ie: intellectual capital, credit risk, and corporate social responsibility) and macroeconomic indicators (ie: nominal GDP growth rate and inflation rate) on the profitability of Islamic banks. The empirical analysis concentrates on the Malaysian Islamic banking industry over the period of nine years, from 2008 to 2016, by applying correlation analysis and multiple regression analysis. The paper finds that greater intellectual capital positively affects the profitability of Islamic banks operating in Malaysia. It means that intellectual capital is the main determinant effects on Malaysian Islamic banks' financial performance. A high intellectual capital exhibits the higher profitability level of Islamic banks. Whereas, credit risk, corporate social responsibility, and nominal GDP growth rate have a strong positive impact on return on equity (ROE) but not return on assets (ROA). Interestingly, there is no positive correlation between the inflation rate and the financial value of Malaysian Islamic banks. Thus, the success of Islamic banks in Malaysia relies on its efficiency of employing resources and profitability.